2014
DOI: 10.12669/pjms.305.5199
|View full text |Cite
|
Sign up to set email alerts
|

Tissue polypeptide antigen & interleukin-6: Are their serum levels a predictor for response to chemotherapy in breast cancer?

Abstract: Objective: To compare the serum level of tissue polypeptide antigen (TPA) and interleukin-6 (IL-6) in women with breast cancer at various stages of the disease and to consider the usefulness of these tumor markers in evaluating the response to chemotherapy. Methods: This case control study included 60 women, from those who were attending the Oncology and Nuclear Hospital in Mosul / Iraq from the period of 1st of March 2012 and 1st of March 2013, complaining of breast cancer of stage 1-4 and receiving chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…IL-6 is secreted by various cell types, including breast cancer cells. The response to IL-6 in such cells depends on the expression of ERs (24). The ER-positive MCF-7 cell line does not secrete IL-6, whereas ER-negative MD-MBA-231 cells do (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 is secreted by various cell types, including breast cancer cells. The response to IL-6 in such cells depends on the expression of ERs (24). The ER-positive MCF-7 cell line does not secrete IL-6, whereas ER-negative MD-MBA-231 cells do (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between CRP and the prognosis of patients with breast cancer remains controversial (18)(19)(20). The association between serum IL-6 expression levels and breast cancer has been reported in treatment prognosis (21)(22)(23) and resistance to chemotherapy (24), and other studies have reported an association between serum IL-6, CRP and breast cancer (25,26). Although previous studies (21-23) have investigated the association between IL-6 and prognosis in patients with metastasis, the prognostic impact of preoperative IL-6 levels remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Historically speaking, Albahlul is a religious person who lived in the Abbasid era, and was known for his ability to get rid of the complicated situations. (12) The story teller is in line with the Muslim merchant`s point of view. He describes him as the one who deserves our sympathy and support.…”
mentioning
confidence: 85%
“…Otherwise, they had nothing but unrest. (18) This feeling of unrest can even be attributed to the economic state the Jewish people faced at that time. Economy is the backbone of the Jewish life and character.…”
mentioning
confidence: 99%
“…In autoimmune disease, IL-6 related abnormal presentation of hepcidin is central to anemia of chronic diseases including RA and SLE. Signifi cant elevation of serum IL-6 is found in breast cancer patients when compared with healthy controls [55,56]. Breast cancer cells may secrete IL-6 to support the proliferation of cancer, and reduction of proliferation of cancer is observed after IL-6 knockdown [57].…”
Section: The Rationale Of Developing Anti-il-6 For the Clinical Theramentioning
confidence: 99%